Online sales and inventory system for Superstoreasia. - Africa, Debbie V. (2011)
The purpose of this study is for the development of online sales and inventory system for SuperStoreAsia. The proponents conducted a study on the existing system used by the company and researched all the possible requirements to develop the proposed system. Thru this, SuperStoreAsia will no longer have a hard time on transacting with their customers and the company will no longer use manual works such as computations and tracking orders. The proponents used Microsoft Visual Studio 2010, ASP.Net-C# and MySQL database in developing the system. They have a time table wherein the development of the system was divided into modules so that they will not feel pressured and face anomalies on doing the system. The proponents learned thoroughly the function on how an online sales and inventory works to develop their programming and documentation skills. Because of that, the proponents developed a flawless system for the benefit of SuperStoreAsia.